DIGITAL FACES OF POLITICAL PARTY IN LOCAL GOVERNANCE: A CASE STUDY OF PARTAI SOLIDARITAS INDONESIA JAKARTA - Sapto Setyo Nugroho; Jufri Yandes (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
This paper examines the dynamics of political party representation in Indonesia with a focus on Partai Solidaritas Indonesia (PSI) in Jakarta, particularly in the context of digital platform usage in the party's role in local governance. The background of this study includes the need to update political analysis in Indonesia in light of the digitization phenomenon affecting political practices, as well as to evaluate the party's presence at the local level, which has often been overlooked in previous studies that concentrated on the national level. PSI Jakarta is chosen as a case study due to its role as a new political party actively engaging in digital activities, making it an ideal representation to explore the digital face of political parties. This study adopts the â€œthree faces of the partyâ€ concept by Katz and Mair, which includes the partyâ€™s face at the organizational level, public office, and grassroots level, to analyze how PSI Jakarta manages these three aspects in its digital platform usage. The research employs a qualitative case study approach, utilizing data collection methods such as observation, interviews, and document analysis. The primary focus of this paper is the relationship between the three faces of the party and the organizational challenges faced by PSI Jakarta, as well as the relevance and implications of these findings for general political party studies. The main findings indicate that PSI Jakarta leverages digital platforms as a tool for interacting with constituents and managing party performance; however, there are still challenges in aligning the three faces of the party proportionally.